(NsTIHOTWORENIQ(B,(NPROZA(B; (NSTATXI PISXMAs (N~ASTX (B2s - (NeSENIN(B, (Ns(B.(Na(B.s (1990)
(Nw NASTOQ]IJ TOM WKL@^ENY STIHOTWORENIQ(B, (NNE WO[ED[IE W OSNOWNOE SOBRANIE(B, (NPROZA PO\TA(B, (NEGO STATXI I PISXMA(B.s
(NsTIHOTWORENIQ(B; (NPROZA STATXI PISXMAs
rus
Keywords: (NsTIHOTWORENIQs; (NPO\MYs